Do women want to talk about birth control at the time of a first-trimester abortion? - Cansino, Catherine; Lichtenberg, E. Steve; Perriera, Lisa K.; Hou, Melody Y.; Melo, Juliana; Creinin, Mitchell D. (Contraception (Stoneham), 2018)
To investigate if women desire talking to a counselor or physician about contraception when seeking first-trimester medical or surgical abortion. We conducted a cross-sectional study by distributing self-administered anonymous surveys to women at three clinics in Sacramento, California; Chicago, Illinois; and Cleveland, Ohio, from October 2014 to February 2015. Participants completed surveys after registration and before any in-office counseling. We asked whether women want to discuss contraception, specific topics they want to discuss, reasons why they may not want to talk about contraception and whether they want to receive contraception services as part of their abortion care. We conducted regression analyses to assess associations between patient characteristics and the desire for counseling. Among 3041 eligible women, 1959 (64.4%) completed surveys. Overall, 1208 (61.7%) did not want to discuss contraception prior to having an abortion, primarily citing that they already know which method they want. We found no association between the desire to discuss contraception and age, race, planned abortion method, clinic site and number of unplanned pregnancies. Among those who desired to talk about contraception, subjects preferred to discuss which contraceptive methods are easier to use and more effective as compared to previously used methods. Regardless of their desire for a discussion about contraception, 1386 (70.8%) of subjects wanted to leave the clinic with a specific method, including a long-acting reversible method [intrauterine device or implant (190, 13.7%)] or other hormonal method [pills, patch, ring or injectable (680, 49.1%)]. The majority of women seeking first-trimester abortion do not come to the clinic wanting to discuss contraception, most commonly because they have a preferred method in mind. Providers should ask women presenting for abortion if they want to discuss contraception and not assume that they need or desire such information. Focused discussions, starting with the preferred method if known, may better satisfy women's preferences. Providers should account for such desires when allocating resources for contraception services during abortion care.